Evaluation of Auditor Functions in Diabetic patients in a tertiary care center, central India - Rakesh Maran,; Vijay Tekam,; Ramit Chaddha,; Kapil Meena, (Asian Journal of Medical Sciences, 2022)
Background: sensorineural hearing loss (SNHL) is the common entity among uncontrolled diabetes patients, mainly in long term hyperglycemia. SNHL is mild to severe in nature. Aims and Objectives: The aims of this study were to evaluate sensory neural hearing loss in patients with diabetes mellitus (DM). Materials and Methods: We undertook that this prospective observational study which includes patients presented with DM to the department of ENT in Chirayu Medical College and Hospital, Bhopal, Madhya Pradesh, was planned for hearing evaluation during period of June 2020-November 2021, total 42 patients of age group 25-65 years were taken for the study. Results: On hearing assessment 29 (69.04%) cases were having SNHL and 13 (30.95%) cases were having normal hearing. Only 10 (23.80%) control were having SNHL and 32 (76.19%) control were having normal hearing. There was statistically significant association found between diabetes and SNHL. SNHL was found in less number of young cases and it was found in most of old age patients. Conclusion: The severity and prevalence of hearing loss are more if duration of hyperglycemia is more and if delay in starting treatment in diabetic child. SNHL is bilateral and mostly mild in the early stage.